Kajian Kombinasi Perlakuan Zat Pengatur Tumbuh TDZ dan Benzil Adenin Terhadap Perkembangan Kalus Durian Merah - Khoirul Bariyyah; Putri Istianingrum (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
Red durian plants have the potential to be developed because they have high economic value. Red durian plants are propagated conventionally in two ways, namely through seeds and shoot grafts. Propagation using shoot graft creates a new problem for red durian farmers, namely a decrease in fruit production on the parent plant due to large amounts of scion. One alternative to the propagation of red durian seeds without damaging the parent plant can be done by using tissue culture techniques. The explants used in this study was durian callus. The callus was grown on B5 media treated with a plant growth regulator combination in the form of TDZ consisting of six treatments, namely 0, 0.4, 0.8, 1.2, 1.6 ppm and BA consisting of five treatment, namely 0, 0.3, 0.6, 0.9, 1.2 ppm. This research was conducted to determine the best dose of combination treatment of tidiazuron (TDZ) with BA in the formation of shoots from red durian callus through tissue culture. The results showed that at the age of 6 months after culture, red durian callus had a color change from yellow to green in the TDZ treatment 1.6 ppm + BA 1.2 ppm.